Correlation Between Prenatal and Postnatal Care of Mothers and Their Child`s Academic Performance - Naul, Stephen; Ortiz, Deznie Jane Novia; Paler, Reinalyn; Morales, Lyka; Nabares, Angelin; Pag-iwayan, Anna Fe (International Journal of Sustainability and Advanced Integrated Research, 2025)
This study examines the relationship between prenatal and postnatal care, maternal socio-demographic factors, and the academic performance of children. The findings suggest that maternal health practices before, during, and after pregnancy significantly influence the cognitive and academic outcomes of their children. Key factors such as the age of conception, maternal educational background, and the intake of essential nutrients like iodine were found to have a significant impact on children’s academic performance. Iodine, in particular, was identified as a crucial nutrient for brain development, with a strong correlation to improved academic outcomes. The study highlights the importance of early prenatal care, adequate nutrition, and maternal education in promoting the academic success of children. Recommendations include early consultations for women planning pregnancy and adequate iodine intake during pregnancy to enhance children’s cognitive development and school performance.